Pengaruh Kompensasi, Motivasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada Wilwatikta Santosa Karanganyar - Rohwiyati, Rohwiyati; Supheni, Indrian (Fakultas Ekonomi - Universitas Setia Budi, 2023)
The purpose of this study was to determine the effect of compensation, motivation and work environment on employee job satisfaction at Wilwatikta Santosa Karanganyar either partially or simultaneously. This research is a quantitative case study. Secondary data is obtained from records or documents. The sample in this study was 39 respondents. The technique used is the census technique while the analysis technique used is multiple linear regression analysis, f test, t test, and coefficient of determination test. The results of this study indicate that partially compensation, motivation and work environment have a significant effect on job satisfaction. These three variables have a significant effect on job satisfaction simultaneously.